Presidential power and democratization by elections in Africa. Issue 4 (19th May 2018) - Morse, Yonatan L.
ABSTRACT: Do elections in and of themselves provide mechanisms for democratization? The "democratization by elections" thesis has been challenged, yet scholars still differ over its substantive effect. Some of the disagreement is over the specific outcome of interest, with proponents advocating for a narrower definition of "democratization". Others want to know more about the factors that condition how elections impact on democracy. This article addresses both points by demonstrating that in Africa the extent of formal presidential power significantly shapes the ability of repeated elections to socialize more broadly democratic behaviour in the form of greater civil and private liberties, more civil society participation, and wider egalitarianism. Using recently available data on African presidents and the democratic qualities of regimes, the article demonstrates the ongoing influence of presidential power in Africa and provides some previously unstudied constraints on the democratization by elections thesis.